The risk profile of rhegmatogenous retinal detachment before and after using a fluoroquinolone: a 12 year nationwide self-controlled case series study. (27th August 2018) - Shin, Ju-Young; Jeong, Sohyun; Jeon, Ha-Lim; Byun, Seongjun; Park, Kyu Hyung; Jeong, Han Eol; Park, Sang Jun
Abstract: Objectives: To determine whether or not fluoroquinolone use increases the incidence of retinal detachment. Design: Self-controlled case series analysis. Participants: Participants were identified using the South Korean National Health Insurance Database between 1 January 2004 and 31 December 2015. A total of 15 134 patients who experienced rhegmatogenous retinal detachment (RRD) with at least one prescription of a fluoroquinolone were included. Methods: Incidence rate ratios (IRRs) and their 95% CIs were calculated using conditional Poisson regression. The main outcome measure was a recorded diagnosis of RRD (ICD-10: H33.0) with a claim for the surgical code for RRD. Results: We found an increased risk of retinal detachment in the first 1–30 days following the initiation of fluoroquinolone therapy (IRR 1.85; 95% CI 1.71–1.95), which rose for the 31–60 days period (IRR 2.05; 95% CI 1.43–2.95) but remained constant after more than 60 days (IRR 1.25; 95% CI 0.75–2.10). However, the elevated risk was also found in the 1–30 day period prior to the initiation of fluoroquinolone therapy (IRR 1.58; 95% CI 1.49–1.68) and also 31–60 days before medication use (IRR 1.11; 95% CI 1.03–1.19). Conclusions: Our case-based study indicated that the risk after fluoroquinolone exposure doubled; however, the risk profile before and after fluoroquinolone use means that the association between fluoroquinolone use and retinal detachment might not be a causal relationship.